Perioperative Management and Anesthesia in Patients with Hemifacial Spasm Undergoing Microvascular Decompression: A Case Report - Agustyawan Pemayun, Tjok Dwi; IGAMW Kurniajaya (HM Publisher, 2023)
Introduction: Microvascular decompression (MVD) is an operation performed to treat a symptom of hemifacial spasm. Hemifacial spasm is described as a disorder of neuromuscular movement characterized by repeated to persistent involuntary contractions affecting the muscles innervated by the facial nerve. Case presentation: A 33-year-old woman came to consciousness with complaints of twitching on the right side of her face since 1 year ago. Initially, the complaint was felt for the first time 3 years ago, only on the upper right eyelid, but it has been getting worse over the past year. Magnetic resonance imaging (MRI) was obtained vascular loop on the right anterior inferior cerebellar artery (AICA) in level cerebellar pontine angle (CPA). MVD is a unilateral neurosurgical procedure in the axial section of the posterior fossa. Positions that can be used are supine and modified lateral decubitus or park bench. The management of anesthesia-related to posterior fossa surgery includes, first, the effect of the drug on the ability of the lungs to hold air from entering the venous circulation. Intravenous administration of anesthetics, for example, fentanyl, can maintain a higher threshold for retaining air bubbles in the pulmonary circulation compared with inhalational anesthetics. Conclusion: Optimal hemodynamic monitoring, good analgesia, and adequate muscle relaxation are the principles of anesthesia monitoring that aim to facilitate the operator in finding access to the disturbed nerve complex.